Combined effect of ultrasound treatment and a mix of Krebs cycle acids on the metabolic processes in Saccharomyces cerevisiae - Permyakova, Larisa; Sergeeva, Irina; Dolgolyuk, Irina; Starovoitova, Kseniya; Atuchin, Victor V.; Vereshchagin, Alexander; Romanenko, Vasiliy; Lashitsky, Sergey (Fermentation)
This article describes the effect of organic acids and ultrasound on the physiological and biochemical properties of yeast, which was used to obtain biologically active peptides. The research featured brewer’s yeast S. cerevisiae W-34/70 cultivated in 11% beer wort. A mix of Krebs cycle acids served as an activator. It included succinic, malic, fumaric, citric, and oxaloacetic acids (1:1:1:1:1). The concentration of the Krebs cycle acids was 1 × 10−10 M/L at 1% to the suspension volume. The ultrasound treatment had an intensity of 10 W/m2 and lasted 3–10 min. The combined effect increased the fermentation activity of the yeast by 98%. The activity of individual biocatalysts of constructive and energy metabolism rose by 108–330%, while that of proteolysis enzymes increased by 15% in comparison with the samples exposed to individual factors. The stimulation increased the rate of amine nitrogen consumption by the yeast. The amount of accumulated amino acids was larger by 80% than in the control, and that of protein larger by 7%. The maximal content of the synthesized protein was reached 1–2 h earlier. The combination of chemical and physical factors intensified the biosynthesis of protein and its intermediates during yeast processing, thus facilitating the subsequent extraction of biologically valuable components.